Biomass Distribution and Productivity in a Poplar Plantation - Kaul, O. N.; Sharma, D. C.; Tandon, V. N. (Indian Forester, 1983)
The distribution of biomass in various tree components and productivity of a 8 years old plantation of Populus deltoides have heen discussed. The total biomass is of the order of 86 tonnes/ha of which 83 per cent is being contributed by the above-ground parts and 17 per cent by the roots.